The characteristics of stationary tourist visit in Maribor between 1961 and 2011 - Horvat, Uroš (Journal for Geography, 2012)
The article discusses the main characteristics of stationary tourist visit in Maribor, the second largest town in Slovenia, in the last half of the century. The main criteria of the tourist visit (number of tourists and overnight stays, share of overnight stays by origin / countries, the average length of stay of tourists, seasonality of tourist visit, distribution of overnight stays by the type of the tourist accommodation, the average occupancy rate of tourist beds) the author analyzes in the major stages of the development of tourism in Maribor. According to the relative short average length of stay of tourists (around 2 days), and other criteria, Maribor is one of the tourist destinations with all characteristics of developed urban tourism.
Keywords: tourism; urban tourism; tourist visit; overnight stays; average length of stay of tourists; Maribor; Slovenia